Anthropoid - Šmejkal, Pavel; Padevět, Jiří (2016)
The book guides the reader through places connected with the activity of the jump group Anthropoid, whose members realized the attack on the deputy reich protector Reinhard Heydrich on 27 May 1942. We visit the place of the jump, the flats of the supporters of the parachutists and the place of the attack itself. In the conclusion of the book, we visit one of the most commemorated places of modern Czech history, the Orthodox Church of Saints Cyril and Methodius in Resslova Street, the place of the last resistance of the parachutists–From back cover